2017
DOI: 10.7324/rjc.2017.1021690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stability Constant of Ternary Intermediate Complex Formation in Mnii Catalysed Periodate Oxidation Of2, 5-Xylidine by Stopped Flow Method

Abstract: Although proposed in many cases, the ternary complexation during periodate oxidation of majority of anilines catalyzed by metals like Mn II , has not been thoroughly subjected to investigations particularly from point of view of evaluation of stability constant of the ternary complex formed and collecting the supporting evidences. In this paper, the formation of ternary intermediate unstable complex 2,5-XYL -Mn II -IO4 -during Mn II catalyzed reduction of periodate by 2,5-xylidine(2,5-XYL) has been explored an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…There are a few reports accessible within the literature concerning the kinetic spectrophotometric estimation of Mn II , based on the reduction of periodate ion by some substrates. [29][30][31][32][33] The reports are available on stability constant for the ternary intermediate complex formation between aromatic amine, Mn II and periodate 34 . Most of the precious metal is very essential for human beings, so these are extracted from waste material.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports accessible within the literature concerning the kinetic spectrophotometric estimation of Mn II , based on the reduction of periodate ion by some substrates. [29][30][31][32][33] The reports are available on stability constant for the ternary intermediate complex formation between aromatic amine, Mn II and periodate 34 . Most of the precious metal is very essential for human beings, so these are extracted from waste material.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Some reports are available on Evaluation of stability constant of ternary intermediate complex formation in Mn II catalyzed periodate oxidation of 2,5-xylidine by stopped flow method. 31 Some aniline was investigated as fabrication of polyaniline nanofiber modified carbon paste electrodes (GOx/MCPE) 32 . The detailed kinetic-mechanistic studies on Mn II catalyzedthe reduction of periodate by p-Bromoanilinehas also been reported.…”
Section: Introductionmentioning
confidence: 99%